Evolution of observables and quasiobservables in classical statistical mechanics - Petrina, D.Ya.; Gerasimenko, V.I.; Kondratiev, Yu.G.; Kuna, T. (Condensed Matter Physics, 2000)
We consider the dual BBGKY hierarchy for quasiobservables of many- particle systems as a basis of nonequilibrium statistical mechanics and give a complete description of the evolution of quasiobservables.